2008
DOI: 10.1007/s10802-008-9283-z
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Traumatic Life Events in a Community Sample of Toddlers

Abstract: Toddlers may be at particularly high risk for a number of psychiatric, developmental and neurobiological consequences in the aftermath of trauma. The social and emotional impact of potentially traumatic life events experienced between 6 and 36-months of age was assessed in an epidemiological birth cohort of 18- to 36-month-olds from the Greater New Haven Area. Event-exposed toddlers evidenced greater symptom severity on the ITSEA Internalizing, Externalizing, Dysregulation, Atypical and Maladaptive scales, as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
54
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 37 publications
3
54
0
Order By: Relevance
“…Young children who are exposed to trauma are also at increased risk of developing emotional and behavioural difficulties (Chemtob et al 2008;Laor et al 1996;Lieberman et al 2005b;Mongillo et al 2009;Zerk et al 2009). However, to date, only two studies have used diagnostic interviews to determine the prevalence of other psychological disorders, besides PTSD, following trauma in young children (Scheeringa and Zeanah 2008;Scheeringa et al 2003).…”
Section: Emotional and Behavioural Difficultiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Young children who are exposed to trauma are also at increased risk of developing emotional and behavioural difficulties (Chemtob et al 2008;Laor et al 1996;Lieberman et al 2005b;Mongillo et al 2009;Zerk et al 2009). However, to date, only two studies have used diagnostic interviews to determine the prevalence of other psychological disorders, besides PTSD, following trauma in young children (Scheeringa and Zeanah 2008;Scheeringa et al 2003).…”
Section: Emotional and Behavioural Difficultiesmentioning
confidence: 99%
“…Young children are also in the highest risk group for accidental trauma, with the majority of burns, falls, driveway runovers, dog attacks and drownings occurring in children under the age of 5 years (Australian Institute of Health and Welfare 2009; Kidsafe QLD 2006). Finally, Mongillo et al (2009) found 23% of toddlers in a community sample had experienced at least one potentially traumatic event between the ages of 6-36 months.…”
mentioning
confidence: 94%
“…To illustrate, samples of justice involved youth across diverse settings have revealed that 33% of Japanese female juvenile offenders (Ariga et al 2008), 27% of Swiss male juvenile offenders (Urbaniok et al 2007), and 10-19% of detained youth in the United States (Abram et al 2004;Cauffman et al 1998;Ford et al 2008;Steiner et al 1997) meet criteria for PTSD. By comparison, in the United States (Copeland et al 2007;Mongillo et al 2009), PTSD is rare among young (ages 0-4) children (0.6% prevalence) and school-age children (1% prevalence), but more common among adolescents (5% prevalence) (Kilpatrick et al 2003).…”
mentioning
confidence: 99%
“…As a result of impairments in selfregulation, youth with complex trauma histories are at elevated risk to develop specific externalizing problems (e.g., hostility, oppositionality, impulsivity) in childhood (Ford et al 1999(Ford et al , 2010bMongillo et al 2009) and adolescence (Farrington 1993;Ford et al 2008Ford et al , 2009Ruchkin et al 2007;Turner et al 2006).…”
mentioning
confidence: 99%
“…In two studies that measured the impact of trauma on toddlers, none of the children in the study fit the formal DSM-IV criteria for PTSD (Mongillo, Briggs-Gowan, Ford, & Carter, 2009). Similarly, among children in treatment for trauma with the National Child Traumatic Stress Network, fewer than a quarter met the criteria for PTSD.…”
Section: Diagnosis Of Early Traumamentioning
confidence: 99%